The Analysis of Proceeding Papers' Coherence through Thematic Progression Manifestation - Imroati Istibsyaroh Ar Ruhimat; Yazid Basthomi; Anik Nunuk Wulyani (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: Twenty research papers published in international conference proceedings are analyzed in terms of its thematic progression manifestation to know the coherence built within the papers. The analysis obtained that among the three thematic progression manifest, zig-zag pattern is the most frequent pattern manifest by 388 patterns, followed by theme reiteration by 317 patterns and multiple rheme by only 8 patterns. This indicates that although the writers are lack of information regarding thematic progression, their unconscious manifestation of thematic progression allows the coherence built within the text, making the readers able to comprehend and understand the papers easily.  Abstrak: Sebanyak 20 artikel yang telah publikasi di prosiding konferensi internasional dianalisis berdasarkan manifestasi Pola Great Tema untuk mengetahui koherensi yang dikembangkan dalam artikel. Diketahui berdasarkan analisis tersebut, dari tiga Pola Gerak Tema yang dimanifestasi, pola zig-zag adalah yang banyak dengan 388 pola, diikuti dengan theme reiteration dengan 317 pola, dan pola multiple-rheme dengan 8 pola. Hasil ini mengindikasikan bahwa, walaupun penulis kurang mendapatkan informasi mengenai Pola Gerak Tema, namun mereka dapat menggunakan Pola Gerak Tema tersebut secara tidak sadar sehingga koherensi dalam artikel terbentuk, dan pembaca dapat mengerti isi artikel tersebut.